New records of alien species Euphorbia davidii in Odesa (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
New records of the alien species Euphorbia davidii Subils in Odessa are reported. In August-September 2022, three new localities of the species were discovered: at the Odesa-Sortuvalna railway station, on the railway bridge and along the tram tracks near the Odesa-Mala railway station. Plants of E. davidii in these localities were well developed, with formed fruits. The largest locality with an area of 400 m2 and with 126 plants was recorded at the Odesa-Sortuvalna railway station. The closest E. davidii sites to the identified localities are in the Odessa region at a distance of 60 km between the railway stations Karolino-Buhaz and Sonyachna. It is expected that further spread of E. davidii will occur both within and outside Odesa along the railroad tracks. Considering that E. davidii is a quarantine object with a high dispersal capacity, its further spread in Ukraine should be monitored.
Keywords: Euphorbiaceae, flora, railway tracks, Ukraine.